A modified version of ceres-maize model for predicting crop response to salinity stress - Castrignanò A.; Katerji N.; Karam F.; Mastrorilli M.; Hamdy A. (Mediterranean crop responses to water and soil salinity: Eco-physiological and agronomic analyses, 2002)
A new saline stress index was developed for CERES-Maize, a computer model of maize growth and development, in order to simulate crop response to irrigation with saline water in Mediterranean conditions. Changes from the original model consisted in modifying the estimation of the stress coefficient, which was defined as a function of predawn leaf water potential. The study was carried out at the Mediterranean Agronomic Institute of Bari using a set-up of 30 drainage lysimeters. Linear regression between mean simulated and measured data showed that the model performed well for final grain yield though it tended to underestimate (a new saline stress index was developed for CERES-Maize, a computer model of maize growth and development, in order to simulate crop response to irrigation with saline water in Mediterranean conditions). Changes from the original model consisted in modifying the estimation of the stress coefficient, which was defined as a function of predawn leaf water potential. The study was carried out at the Mediterranean Agronomic Institute of Bari using a set-up of 30 drainage lysimeters. Linear regression between mean simulated and measured data showed that the model performed well for final grain yield though it tended to underestimate ( ~8 percent) above-ground biomass and maximum LAI. The largest evapotranspiration over-estimations were found early in the growing season immediately after each irrigation event. However, the prediction of seasonal evapotranspiration was generally reasonably good.